The Pain Truth: Recognizing the Influence of Pain on Cosmetic Outcomes - Dayan, Steven H. (Facial Plastic Surgery, 2014)
Anxiety is an under recognized and major obstacle among patients seeking cosmetic procedures. The ability to alleviate it may be essential for achieving high patient satisfaction and better outcomes. Key initiators leading to anxiety include the fear of appearing unnatural and the fear of pain. Pain perception can be mitigated or augmented by psychological factors. Based on patient expectations, they may experience diminished pain perception through the placebo effect or catastrophized pain due to previous painful experiences. It is also important to recognize the influence of religion, cultural, ethnic, and gender bias on pain perception. In recent years, the aesthetic medical community has responded to patient demand for more minimally invasive procedures with more natural appearing result, resulting in a dramatic increase in the number of cosmetic procedures performed each year. Achieving pain and anxiety-free aesthetic medicine will likely result in a pronounced increase in the demand for cosmetic treatments.
Keywords: pain; anxiety; fear; cosmetic medicine; patient satisfaction